Leptin : a pleitropic factor in physiology / Fayez A Almabhouh … [et al.] - Almabhouh, Fayez A; Ahmad Muhammad, Faizatul Isyraqiah; Ibrahim, Hisham; Singh, Harbindarjeet (Universiti Teknologi MARA Cawangan Selangor, 2019)
Leptin, a 16 kDa protein and a product of the ob/ob gene, has a tertiary structure similar to that of a cytokine. It is primarily secreted by white adipose tissue and its levels in the blood correlate positively with percentage body fat. Leptin was first identified in 1994 as a major factor that regulated food intake and energy balance. Leptin in the circulation exists either as a free monomeric hormone or bound to its soluble receptor. Its serum levels usually range from 0.5 to 37.7 ng/ml in males and 2.0 to 45.2 ng/ml in females. The half-life of leptin is between 20 - 30 minutes and it is eliminated mainly by the kidneys. However, research over the last 25 years has revealed numerous other physiological roles for leptin, including roles in inflammation, immune function, neuro-endocrine function, bone metabolism, blood pressure regulation and sexual maturation. Most of these roles have been identified from studies on leptin deficient rodents. Apart from energy balance and sexual maturation, where its role is direct and obvious, its actions on the rest of the other systems are permissive. Actions of leptin are both centrally and peripherally mediated involving receptors that are widely distributed in the body. Six leptin receptor isoforms, belonging to the class 1 cytokine receptor family, have been identified. These receptors are products of the OBR gene. The cellular actions of leptin are mediated through any one of five different signalling pathways that include the JAK-STAT, PI3K, MAPK, AMPK, and the mTOR signalling pathways.